Filling of voids in coal longwall mining with caving – technical, environmental and safety aspects - Palarski, J.; Plewa, F.; Strozik, G. (Mine Fill 2014: Proceedings of the Eleventh International Symposium on Mining with Backfill, 2014)
In the majority of mining operations in the Upper Silesia Coal Basin, the longwall mining method with caving is being used. Control of the roof by caving has numerous technical advantages and does not generate additional costs which, in case of traditional hydraulic backfill, can easily make mining operations unprofitable. However, the presence of caving zones generates many problems related to the stability of the rock mass and mine subsidence, water and gas permeability, spontaneous coal ignition, methane hazard etc., which generally are considered environmental and safety issues. It is important that filling of voids in cavings (grouting) does not interfere with mining production and does not involve significant additional costs. An important part of the paper is dedicated to the assessment of the receptivity of cavings. Results of measurements of volumes of fill mixture placed in cavings of 65 Polish coal mines are presented and discussed. Due to the lack of direct observations of caving filling results, a statistical assessment method was adopted, considering the highest ration of measured fill volumes to extraction volumes as the receptivity. The application of this technology may be considered in environment protection terms, like the utilisation of waste and saline waters, the improved stability of the rock mass, the reduction of gas and groundwaters migration into the rock mass, etc. Technologies of filling of voids in cavings adopted in the Polish coal mining industry are also presented in the paper, from current problems and a further development point of view. Physical properties and requirements for fill materials and mixtures are discussed. Limitations and issues with the application of this technology, which occur in mining practices, are also presented and discussed.